Virus-specific host responses and gene signatures following infection with major SARS-CoV-2 variants of concern: role of ZBP1 in viral clearance and lung inflammation - Elsharkawy, Amany; Jahantigh, Hamid Reza; Guglani, Anchala; Stone, Shannon; Arora, Komal; Kumar, Mukesh (Frontiers in Immunology, 2025)
SARS-CoV-2 can cause severe lung damage due to uncontrolled viral replication or/and excessive inflammation. New variants of concern (VOCs) have raised additional concerns due to disparate pathogenicity and possible enhanced virulence. Herein, using RNA sequencing, we performed a comparative transcriptomic analysis following infection with major VOCs. We evaluated the transcriptional changes induced in the lungs of K18-hACE2 mice following infection with the ancestral B.1 lineage (Wuhan), B.1.1.7 (Alpha), B.1.351 (Beta), B.1.617.2 (Delta), B.1.1.529 (Omicron) variants or mouse-adapted SARS-CoV-2 (MA10). Our work reveals the molecular basis of pathological hallmarks in the lungs associated with SARS-CoV-2 infection. We report that infection with B.1, pre-Omicron VOCs, and MA10 induce similar molecular fingerprints of excessive lung inflammation and immune activation in K18-hACE2 mice. Analysis of differentially expressed genes revealed both shared and variant-specific responses, with key immune markers such as Cxcl10, Zbp1, Ifit3, Isg15, Rsad2, and Irf7 consistently upregulated across variants. Clustering of highly variable genes across samples revealed two variant groups distinguished by upregulation of antigen presentation and immune-related genes (e.g. Retnla, Saa3, Plac8, Ly6c2, H2-D1, and H2-K1). Delta, Beta, Alpha, and MA10 showed elevated expression, whereas Wuhan and Omicron exhibited attenuated responses. In addition, we show that Z-DNA-binding protein 1 (ZBP1) plays a role in viral clearance in the lungs after SARS-CoV-2 infection. ZBP1 deficiency resulted in reduced expression of cell death-associated markers and virus-induced cell death in the lungs following MA10 infection. Furthermore, the knockout of ZBP1 resulted in an attenuated inflammatory response with reduced production of proinflammatory cytokines and chemokines and decreased macrophage infiltration in the lungs. These results suggest that ZBP1 plays a role in viral clearance and in enhancing the inflammatory response and virus-induced cell death during SARS-CoV-2 infection. Altogether, our study provides insights into the pathogenesis of SARS-CoV-2 infection in mice, facilitating the identification of biomarkers and the development of potential therapeutic targets.